Developments in Managing and Exploiting Risk. Socio-Political Risk Management : Assessing and Managing Global Insecurity - Kurt J. Engemann; Cathryn F. Lavery; Jeanne M. Sheehan (Developments in Managing and Exploiting Risk. Socio-Political Risk Management : Assessing and Managing Global Insecurity, 2023)
Managing risk necessitates an understanding of both how to avoid detrimental outcomes and to reap beneficial results. Organizations are regularly confronted with complex decisions involving risk and the impending consequences of the negative impact of its manifestation. However, the positive aspects of embracing risk should also be sufficiently evaluated to obtain a full assessment of opportunities. Socio-Political Risk Management: Assessing and Managing Global Insecurity covers a range of viewpoints and issues which can be applied to various organizational agency structures. These perspectives examine how social and political risk can impact an agency, and what recommendations are made to adapt, mitigate, and strengthen the organization against political risk. Accessibility to personnel and agencies via social media, the internet and public exposure compounded with political and social societal shifts have led many agencies in a constant spin to assuage and sustain viability and relevance publicly. Socio-Political Risk Management: Assessing and Managing Global Insecurity serves the readers by raising awareness and the necessity to control social and political risks in their organizations. This volume explores pathways for those in differing organizational structures to find common threads pertaining to social and political risks. An important goal of the work is also to develop a framework for managing and exploiting risk that can be applied at the organizational level
10.1515/9783110731217; 10.1515/9783110731217